PENDEKATAN KONTEKTUAL MELALUI METODE PENUGASAN UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS VII SMPN 2 KUTASARI PURBALINGGA - Jaka Dwi Irianta; Sulistyo Herawati (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2015)
The objective of the research is to know the task-based method to improve the students’ achievement  in local content PKK of the seventh grade students. The type of the research is a classroom action research. The population is 188 students, consisting of all students at the seventh grade of SMPN 2 Kutasasri. The sampling technique  is purposive random sampling by class VII D as a sample. The data are collected by test. To analyze the data, it uses descriptive quantitative analysis. The result show that the effort of  teacher in improving the students achievement through task based method for the seventh grade students is categorized gog. It means that the implementation of the method is effective. The average score of post test is 74.58 with students. Complete learning above 70 meaning that it has met the expectation of the researcher.